Employment effects of increased inland waterway transport in the Danube region - Österreichisches Institut für Wirtschaftsforschung, Vienna; Schönfelder, Stefan; Streicher, Gerhard; Gille, Johan; Trosky, Frank (Vienna, 2015)
"The promotion of Inland Waterway Transport (IWT) is one of the political priorities of the "European Union Strategy for the Danube Region". A growing share of IWT within the regional freight transport market is expected to raise the sustainability of the transport system and provide beneficial regional economic effects. Relatively high energy efficiency and good environmental performance, together with low specific costs, rank among the primary advantages of this transport mode. The study "Danube+20" initiated by the European Commission looked at the employment effects of a 20 percent increase in IWT transport volume in the Danube region by 2020 compared to 2010. The results of the simulation using the multi-regional input-output model ADAGIO indicate that IWT offers a source of moderate additional employment for the river's bordering regions. The employment growth mainly results from induced economic effects, i.e., reduced average transport costs for the entire economy."